Combined probiotics with vitamin D3 supplementation improved aerobic performance and gut microbiome composition in mixed martial arts athletes - Przewłócka, Katarzyna; Folwarski, Marcin; Kaczmarczyk, Mariusz; Skonieczna-Żydecka, Karolina; Palma, Joanna; Bytowska, Zofia Kinga; Kujach, Sylwester; Kaczor, Jan Jacek (Frontiers in Nutrition, 2023)
Introduction: Mixed Martial Arts (MMA) is characterized as an interval sport in which the training program focuses on enhancing both aerobic and anaerobic capacities. Therefore, strategies targeting the intestinal microbiome may be beneficial for MMA athletes. Moreover, vitamin D supplementation may amplify the positive effects of certain bacterial strains. We previously demonstrated that the combined of probiotics and vitamin D3 supplementation improved the lactate utilization ratio, total work, and average power achieved during anaerobic tests in MMA. Therefore, this study aimed to investigate whether combined probiotic and vitamin D3 ingestion can modify the composition of the gut microbiome and epithelial cell permeability, influence the inflammatory response, and ultimately enhance aerobic capacity.Methods: A 4-week clinical trial was conducted with 23 male MMA athletes randomly assigned to either the probiotic + vitamin D3 (PRO+VIT D) group or the vitamin D3 group (VIT D). The trial employed a double-blind, placebo-controlled design and involved measurements of serum inflammatory markers, gut microbiome composition, epithelial cell permeability, and aerobic performance.Results: After 4-week of supplementation, we found a significantly lower concentration of calprotectin in the PRO+VIT D group (34.79 ± 24.38 mmol/L) compared to the value before (69.50 ± 46.91) supplementation (p = 0.030), augmentation of beta diversity after the intervention in the PRO+VIT D group (p = 0.0005) and an extended time to exhaustion to 559.00 ± 68.99; compared to the value before (496.30 ± 89.98; p = 0.023) after combined probiotic and vitamin D3 supplementation in MMA athletes. No effect was observed in the VIT D group.Our results indicate that combined treatment of probiotics and vitamin D3 may cause alterations in alpha and beta diversity and the composition of the gut microbiota in MMA athletes. We observed an improvement in epithelial cell permeability and an extended time to exhaustion during exercise in MMA athletes following a 4-week of combined probiotic and vitamin D3 treatment.